2012
DOI: 10.2478/v10102-012-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Teratology – past, present and future

Abstract: Teratology is the science that studies the causes, mechanisms, and patterns of abnormal development. The authors present an updated overview of the most important milestones and stages of the development of modern teratology. Development of knowledge and society led to the recognition that causes of congenital developmental disorders (CDDs) might be caused by various mechanical effects, foetal diseases, and retarded or arrested development of the embryo and foetus. Based on the analysis of the historical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 56 publications
0
19
0
6
Order By: Relevance
“…Among 1396 different substances studied, it has been shown that half of the human teratogens are safe in animals. Conversely, almost half of the safe human agents are dangerous (teratogen) in animals, and 1/3 tested agents showed varying results in different species [62][63][64].…”
Section: Teratogenicitymentioning
confidence: 99%
“…Among 1396 different substances studied, it has been shown that half of the human teratogens are safe in animals. Conversely, almost half of the safe human agents are dangerous (teratogen) in animals, and 1/3 tested agents showed varying results in different species [62][63][64].…”
Section: Teratogenicitymentioning
confidence: 99%
“…La teratología nos brinda ejemplos de eso (UJházy et al, 2012). La perturbación de los procesos de inducción embrionaria, que son los responsables de la diferenciación de órganos en la ontogenia, puede generar distintas malformaciones; y esas perturbaciones pueden ser apuntadas como causas de dichas anomalías sin que para ello sea necesario conocer la base molecular de tales fenómenos (GILbErT, 1994, p. 513-515;DELSoL & PErrIn, 2000, p. 88-90).…”
Section: Explicaciones Anómicasunclassified
“…The damaging effects of electromagnetic fields depend on the frequency (wavelength), the density of the field, and the duration of radiation (1). Extremely low frequency electromagnetic fields (ELF-EMF), non-ionizing radiation that has a frequency range in home appliances with frequency of 50 or 60 Hz that emit waves with long wavelength (3). Most electrical appliances work in the frequency range between 50 and 60 Hz, and further studies of the impact of electromagnetic radiation on living organisms is being done in this frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…Most electrical appliances work in the frequency range between 50 and 60 Hz, and further studies of the impact of electromagnetic radiation on living organisms is being done in this frequency range. Fifty Hertz corresponds to a wavelength of 3,500 kilometers, which is close to the Earth’s radius (3). Many studies have been conducted to determine the possible effects of low frequency fields on human health (46).…”
Section: Introductionmentioning
confidence: 99%